Rabies Virus Infection: A Case Series and Literature Review - Shiva Shadani; Fahimeh Ghasemi; Mahsa Kamali; Mohammad Reza Navaeifar; Ahmad Alikhani; Shahriar Alian; Alireza Davoudi Badabi; Mohammad Sadegh Rezai (Mazandaran University of Medical Sciences, 2022)
Background: Rabies is a fatal and often neglected disease leading to encephalomyelitis following a bite by an infected mammal. According to the necessity of rabies disease in Iran, we present four cases of rabies virus infection.  Case Presentation: We presented 4 cases of rabies virus infection hospitalized in different hospitals in Iran in 2021-2022. Three patients were male. The youngest patient was 6 years old and the oldest was 81 years old. In all 4 cases, RT-PCR detected the positive virus infection. Three cases received rabies immunoglobulin. All of them received at least one dose of rabies vaccination; but, unfortunately, all patients died. Conclusions: The present case series showed the necessity of early rabies vaccination and also the early organization of stray dogs in the community. Unfortunately, two cases were lost to follow-up. So, the population education and follow-up of suspected rabies patients must be taken seriously by healthcare facilities.